An Enigmatic radical expression.

12345689654321233 + 5333334096 12345679 12345689654321233 5333334096 12345679 3 = ? \small \sqrt[3]{\sqrt{\sqrt{12345689654321233 + 5333334096 \sqrt{12345679}}} - \sqrt{\sqrt{12345689654321233 - 5333334096\sqrt{12345679}}}} = ?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Sep 30, 2019

Let x x be the number we need to find and ( a + b 12345679 ) 2 = 12345689654321233 + 5333334096 12345679 (a+b\sqrt{12345679})^2 = 12345689654321233 + 5333334096 \sqrt{12345679} . Then

x = a + b 12345679 a b 12345679 3 Let ( c + d 12345679 ) 2 = a + b 12345679 = c + d 12345679 c d 12345679 3 \begin{aligned} x & = \sqrt[3]{\sqrt{a+b\sqrt{12345679}} - \sqrt{|a-b\sqrt{12345679}|}} & \small \color{#3D99F6} \text{Let } (c+d\sqrt{12345679})^2 = a+b\sqrt{12345679} \\ & = \sqrt[3]{c+d\sqrt{12345679} - \left|c-d\sqrt{12345679}\right|} \end{aligned}

( a + b 12345679 ) 2 = 12345689654321233 + 5333334096 12345679 a 2 + 12345679 b 2 + 2 a b 12345679 = 12345689654321233 + 5333334096 12345679 \begin{aligned} (a+b\sqrt{12345679})^2 & = 12345689654321233 + 5333334096 \sqrt{12345679} \\ a^2+ 12345679 b^2 + 2ab\sqrt{12345679} & = 12345689654321233 + 5333334096 \sqrt{12345679} \end{aligned}

{ a 2 + 12345679 b 2 = 12345689654321233 . . . ( 1 ) a b = 2666667048 . . . ( 2 ) \implies \begin{cases} a^2+ 12345679 b^2 = 12345689654321233 & ...(1) \\ ab = 2666667048 & ...(2) \end{cases}

a 2 ( 1 ) : a 4 + 12345679 ( a b ) 2 = 12345689654321233 a 2 ( 2 ) : a b = 2666667048 a 4 12345689654321233 a 2 + 87791520219480508137172416 = 0 a = 111111127 b = 12 \begin{aligned} a^2(1): a^4+ 12345679 ({\color{#3D99F6}ab})^2 & = 12345689654321233a^2 & \small \color{#3D99F6} (2): \ ab = 2666667048 \\ a^4 - 12345689654321233a^2 + 87791520219480508137172416 & = 0 \\ \implies a & = 111111127 \\ b & = 12 \end{aligned}

Similarly,

( c + d 12345679 ) 2 = 111111127 + 24 12345679 c 2 + 12345679 d 2 + 2 c d 12345679 = 111111127 + 24 12345679 \begin{aligned} (c+d\sqrt{12345679})^2 & = 111111127 + 24 \sqrt{12345679} \\ c^2+ 12345679 d^2 + 2cd\sqrt{12345679} & = 111111127 + 24 \sqrt{12345679} \end{aligned}

{ c 2 + 12345679 d 2 = 111111127 . . . ( 3 ) c d = 24 . . . ( 4 ) \implies \begin{cases} c^2+ 12345679 d^2 = 111111127 & ...(3) \\ cd = 24 & ...(4) \end{cases}

c 2 ( 1 ) : c 4 + 12345679 ( c d ) 2 = 111111127 c 2 ( 2 ) : a b = 2666667048 c 4 111111127 c 2 + 1777777776 = 0 c = 4 d = 3 \begin{aligned} c^2(1): c^4+ 12345679 ({\color{#3D99F6}cd})^2 & = 111111127c^2 & \small \color{#3D99F6} (2): \ ab = 2666667048 \\ c^4 - 111111127c^2 + 1777777776 & = 0 \\ \implies c & = 4 \\ d & = 3 \end{aligned}

Therefore

x = 4 + 3 12345679 4 3 12345679 3 = 4 + 3 12345679 ( 3 12345679 4 ) 3 = 8 3 = 2 \begin{aligned} x & = \sqrt[3]{4+3\sqrt{12345679} - \left|4-3\sqrt{12345679}\right|} \\ & = \sqrt[3]{4+3\sqrt{12345679} - (3\sqrt{12345679}-4)} \\ & = \sqrt[3] 8 = \boxed 2 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...